Sensitivity Versus Size: Implications for Tax Competition - David R. Agrawal; Adib Bagh; Mohammed Mardan (CESifo GmbH, 2025)
The conventional wisdom is that a big jurisdiction sets a higher tax rate than a small jurisdiction. We show this result arises due to simplifying assumptions that imply tax-base sensitivities are equal across jurisdictions. When more than two jurisdictions compete in commodity taxes, tax-base sensitivities need not be equal across jurisdictions and a small jurisdiction can set a higher tax rate than a big jurisdiction. Our analysis extends to capital and profit taxes, and, more generally, to various types of multi-player asymmetric competition.
Keywords: C70; D40; H20; H70; L10; R50; 330; Ramsey rule; inverse elasticity; fiscal competition; optimal taxation; spatial price competition; sales tax